2012
DOI: 10.1002/ird.1680
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Intensity and Soil Physical Properties Influence on Infiltration and Runoff Under In‐field Rainwater Harvesting Conditions

Abstract: The objective of this study was to quantify the combined influence of rainfall intensity and soil physical properties on infiltration and runoff under in‐field rainwater harvesting (IRWH). Rainfall intensities and soil physical properties were mathematically related to time to runoff, time to final infiltration rate and final infiltration rate. The influence of rainfall intensity and soil physical factors on rainwater harvesting under IRWH was demonstrated. A commercial field, divided into 75 plots and under I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…Mzezewa and van Rensburg (2011) and Tesfuhuney et al (2013) addressed the rainfall intensity and runoff-rainfall relationship. Bothma et al (2012) documented the role of soil physical properties on the rainfall-runoff relationship. Zerizghy (2012) investigated the evaporation on the runoff area during a fallow period.…”
Section:  Conventional Tillagementioning
confidence: 99%
“…Mzezewa and van Rensburg (2011) and Tesfuhuney et al (2013) addressed the rainfall intensity and runoff-rainfall relationship. Bothma et al (2012) documented the role of soil physical properties on the rainfall-runoff relationship. Zerizghy (2012) investigated the evaporation on the runoff area during a fallow period.…”
Section:  Conventional Tillagementioning
confidence: 99%
“…Several studies have shown that time to runoff decreased significantly with increasing rainfall intensity [28,29]. In our study, the time to runoff is listed in Table 2 at about 2 min, 1 min and 0.5 min under RI of 0.4 mm min -1 , 1.0 mm min -1 and 1.8 mm min -1 , respectively, which is consistent with the results of Bothma et al [28]. Furthermore, the negative relationship between the slope gradient and t p indicated that steep slope intensified the decrease rate as shown in Fig.…”
Section: N Transfer To Runoff In Response To Various Ris and Sgsmentioning
confidence: 99%
“…From the soil type the main factors are soil textural and structural pore size distribution (Leonard and Andrieux, ), soil depth (Ffolliott et al ., ), antecedent soil water content (Mayor et al ., ), and presence of impervious horizon(s) in the soil profile (Zhang et al ., ). Ground surface related factors are presence of crust (Bothma et al ., ; Zhao et al ., ), type and density of vegetal cover (Mayor et al ., ; Zhao et al ., ) and slope gradient (Zhang et al ., ). Other ground factors include soil surface structure, organic carbon content, roughness, stoniness, and presence and distribution of cracks, bio‐channels and fissures (Mayor et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Other ground factors include soil surface structure, organic carbon content, roughness, stoniness, and presence and distribution of cracks, bio‐channels and fissures (Mayor et al ., ). From the rainstorm aspect the main factors are rainstorm intensity (Bothma et al ., ; Zhao et al ., ), amount (Martinez‐ Mena et al , ) and duration (Zhang et al ., ). Other authors have cited evaporation to be a key factor influencing infiltration especially in drylands even though most of the research has been carried out in temperate climates (Leornard and Andrieux, ; Castillo et al ., ; Zhang et al ., ).…”
Section: Introductionmentioning
confidence: 99%